Effect of Change in Plant Capacity towards Controllability of Biohydrogen Production Plant from Biomass - Abdul Wahid; Rizali Nurcahya Nararya; Shafira Anandita (Journal of Engineering)
This paper discusses the plant-wide control system of a biohydrogen plant from biomass. The plant’s control structure is designed by assessing the use of model predictive control (MPC) and proportional-integral (PI) controllers for each controlled variable. Then, the control structure design is tested by set point and disturbance change tests, and its performance is evaluated by integral square error (ISE). This plant is simulated in two different capacities to understand the effect of change in plant capacity on the plant’s controllability. Results show that the plant with capacity A has controllability of +25% and −5%, while the plant with capacity B has controllability of +100% and −5% for the dry biomass molar flow rate change test. Both plants have the same controllability of +100% and −100% for the dry biomass temperature test. Both plants result in a dry biomass conversion rate of 16.52%, where the amount of H2 produced is 382 kg/h and 2,291 kg/h, respectively.